2009
DOI: 10.1245/s10434-009-0789-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diabetes Mellitus and Long-Term Survival After Resection of Pancreatic Adenocarcinoma

Abstract: Preexisting DM is associated with reduced survival in patients undergoing resection for PDAC. PDAC with new-onset DM may exhibit increased tumor size and decreased postresection survival. Additional investigation is needed to clarify etiology and impact of PDAC-associated DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 43 publications
6
96
4
1
Order By: Relevance
“…9 In a related study using a similar patient population, although assessing longterm outcomes, this group did find that new-onset DM (<24 months before the diagnosis of PDAC) was predictive of poorer OS, independent of tumor characteristics and related comorbidities, such as BMI. 15 Interestingly, preoperative DM, regardless of time of onset, was also independently associated with increased tumor size. Our novel finding that preoperative insulin use is an independent predictor of both early postoperative mortality and OS suggests that hyperinsulinemia itself may be responsible for some of the findings described above.…”
Section: Discussionmentioning
confidence: 90%
“…9 In a related study using a similar patient population, although assessing longterm outcomes, this group did find that new-onset DM (<24 months before the diagnosis of PDAC) was predictive of poorer OS, independent of tumor characteristics and related comorbidities, such as BMI. 15 Interestingly, preoperative DM, regardless of time of onset, was also independently associated with increased tumor size. Our novel finding that preoperative insulin use is an independent predictor of both early postoperative mortality and OS suggests that hyperinsulinemia itself may be responsible for some of the findings described above.…”
Section: Discussionmentioning
confidence: 90%
“…This survival benefit of metformin was particularly notable because patients with a preoperative diagnosis with diabetes have been shown to have worse outcomes and thus a worse OS. 29,30 After accounting for differences in baseline risk factors including nodal status, metformin use was associated with a 21 % improved survival. Interestingly, we also observed a dose-effect with an increasing daily dose of metformin associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al examined the records of resected PC patients and found that preexisting diabetes is associated with reduced survival in patients who underwent resection for PC. Additionally, PC with new-onset diabetes may exhibit increased tumor size and decreased postresection survival [34]. When hamster H2T pancreatic carcinoma cells were implanted into the cheek pouches of Syrian hamsters, the tumor size, weight, and total DNA content were significantly greater in animals with diabetes, demonstrating that diabetes appears to promote the growth of PC cells in the hamster [35].…”
Section: Hyperglycemia and Cancer Cell Proliferationmentioning
confidence: 99%